2017
DOI: 10.1002/sia.6313
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, optical, and structural characterization of p‐type N‐doped SnO thin films prepared by thermal oxidation of sputtered SnNx thin films

Abstract: We present a study of electrical and optical properties of nitrogen-doped tin oxide thin films deposited on glass by the DC Magnetron Sputtering method. The deposition conditions to obtain p-type thin films were a relative partial pressure between 7% and 11% (N 2 and/or O 2 ), a total working pressure of 1.8 mTorr and a plasma power of 30 W. The deposited thin films were oxidized after annealing at 250°C for 30 minutes. X-ray diffraction results showed that the asdeposited thin films exhibit a Sn tetragonal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…27,28 SnO x thin film, which enhances its p-type mobility. 3,21,29 Figure 3A also shows the effect of annealing on XRD measurements for three samples of SnO x deposited at a ppO 2 of 8.0% and annealed to 160 C, 180 C, and 200 C. These three patterns reveal a mixture of Sn and SnO crystalline phases; however, the film annealed at 160 C presented a peak at 44.9 , which suggests there is an amount of Sn traces higher than that in the other two films. In the sample annealed at 200 C, the intensity of the SnO XRD peaks was reduced, and the intensity of the (110) peak increased compared with the intensity of the (101) peak.…”
Section: Methodsmentioning
confidence: 97%
“…27,28 SnO x thin film, which enhances its p-type mobility. 3,21,29 Figure 3A also shows the effect of annealing on XRD measurements for three samples of SnO x deposited at a ppO 2 of 8.0% and annealed to 160 C, 180 C, and 200 C. These three patterns reveal a mixture of Sn and SnO crystalline phases; however, the film annealed at 160 C presented a peak at 44.9 , which suggests there is an amount of Sn traces higher than that in the other two films. In the sample annealed at 200 C, the intensity of the SnO XRD peaks was reduced, and the intensity of the (110) peak increased compared with the intensity of the (101) peak.…”
Section: Methodsmentioning
confidence: 97%
“…Many methods have been pursued to prepare tin nitride thin films, including chemical vapor deposition (CVD), plasma-enhanced CVD, magnetron, or radio-frequency (RF) sputtering [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Among these, RF sputtering is the most frequently used technique to grow tin nitride thin films from tin in a nitrogen-containing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the above limitations, the utilization of the new approaches to synthesizing SnO plays a key role in improving the SnO film properties. Garzon-Fontecha et al 12) showed that SnO film deposition in a nitrogen-containing atmosphere can lead to the substitution of O and Sn atoms by nitrogen ones. This substitution leads to changes in the optical and electrical properties, including a decrease in transmittance and an increase in the carrier concentration of holes.…”
Section: Introductionmentioning
confidence: 99%